Upaya Guru Agama Islam dalam Mengatasi Problematika Kenakalan Remaja (Studi Kasus di SMA Avicenna Mojongapit Jombang) - A. Syafi' As; Yulia Rahmawati (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
Abstract This study aims to determine the efforts of Islamic religious education teachers in overcoming the problem of juvenile delinquency of Avicenna Mojongapit High School Jombang. The data sources of the research are informants, events / activities, and documentation / archives. Data collection uses observation, interview and documentation techniques. Data analysis using descriptive qualitative method. Results: Forms of juvenile delinquency (students) in Avicenna Mojongapit Jombang High School, including violating school uniform provisions, going home and going out at effective hours without information, not doing homework, skipping, late coming and smoking in the school area. Factors that cause delinquency of students in Avicenna Mojongapit Jombang High School consist of Internal Factors and External Factors The efforts of Islamic Education teachers in overcoming delinquency problems in Avicenna Mojongapit Jombang High School are Preventive (through prevention) through Islamic Religious Activities, and are curative with give admonitions and advice, special attention, guidance with love and affection to students who have problems. Keywords: The Teacher of Islamic Education, Problems, Juvenile Delinquency